Forward deployed coil embolization with multiple overlapping stents for ruptured blood blister-like aneurysms: technical considerations and outcomes. (3rd June 2019) - Kim, Myeong Jin; Chung, Joonho; Shin, Yong Sam; Lim, Yong Cheol
ABSTRACT: Background : Coil embolization with multiple overlapping stents was performed as an alternative treatment option for blood blister–like aneurysms (BBAs). However, coil placement into the BBAs has the inherent risks of rupture and regrowth. We describe a safe dense coil packing technique into and just proximal of BBAs using a semi-jailing technique for the treatment of BBAs of the internal carotid artery (ICA) and report the long-term clinical outcomes. Methods : The technique involves the partial deployment of a self-expanding and retrievable stent from the ICA bifurcation to the mid-portion of a BBA followed by coil embolization with gradual unsheathing of the stent from the BBA to its just proximal portion. Seventeen patients were treated using this technique (10 women; mean age, 47.9 ± 11 years; overall mean clinical follow-up period, 42.3 ± 22.8 months). Technique safety and feasibility, and follow-up angiographic results and clinical outcomes (modified Rankin Scale, mRS) were evaluated. Results : Procedures were successfully applied without any procedure-related complications. Immediate post-treatment angiograms showed total obliteration of the BBAs in all 17 patients. Follow-up angiograms, which were available in 15 (88.2%) patients, showed complete resolution of BBAs. Fourteen (82.4%) of 17 patients achieved favorable clinical outcomes (mRS ≤ 2). Conclusions : Forward deployed coil embolization with multiple overlapping stents offers a safe and effective reconstructive endovascular technique for the treatment of the BBAs.